Green Synthesis of Iron Oxide Nanoparticles and Their Modification with CTAB for the Decolorization of Dye Reactive Blue 238 - Al- Rubai, Hasan Fadhil; Al-dahan, Atyaf Khalid Hameed; Jasim, Ban A. (Iraqi Journal of Science, 2023)
Magnetized iron oxide nanoparticles (NPs) were prepared using Eucalyptus leaf extract and then coated with CTAB (Cetrimonium bromide) to increase efficiency. The prepared and modified (NPs) were characterized using AFM, FTIR, and X-ray techniques. The adsorption of the dye reactive blue RB 238 on coated (NPs) was investigated. The effect of various experimental factors, such as the initial concentration of the dye, the amount of adsorbent, pH and temperature on the removal of RB238 was studied. The best conditions for dye removal were found to be 298 K in an acidic medium of pH = 3 and an appropriate dose of the adsorbent of 0.15 g per 25 mg/L to achieve the best color removal of 90% within 60 minutes. The pseudo-second-order reaction model gave results more suitable for experimental facts than the pseudo-first-order reaction model.